Preservation of Cultural and Historical Heritage of Northern Kazakhstan Using Three-Dimensional Technologies - Mukhamadeyeva, R.; Mukhamadeyeva, I.; Alkafafi А. (Journal of Posthumanism, 2025)
This study explores various criteria for assessing cultural and historical heritage, emphasizing the role of social practice in providing an objective evaluation of the historical, scientific, and artistic significance of heritage sites. The primary objective of this research is to enhance knowledge and ensure the preservation of the cultural and historical heritage of Northern Kazakhstan through the application of digital technologies. First, the study examines the criteria for including Kazakhstan’s cultural and historical sites in the UNESCO World Heritage List, analyzing their relevance and proposing a weighted characteristic method to prioritize historical monuments in Northern Kazakhstan for digitization. Second, it introduces the use of three-dimensional (3D) technologies as a means of preserving cultural and historical heritage. This approach represents the first initiative in Kazakhstan aimed at developing a digital database of cultural and historical objects, aligning with the national program Digital Kazakhstan.The creation of a digital repository of historical and cultural sites will facilitate access to historiographical materials on Northern Kazakhstan, enhance the effectiveness of scientific research, and promote integration into the global academic community. Moreover, through web technologies, these digital models will be widely accessible to scholars, government institutions, and the general public. The findings of this study contribute to the development of digital models that can be utilized by various stakeholders, including governmental bodies responsible for heritage conservation. Additionally, the results can serve as educational resources in the teaching of historical disciplines at secondary and higher education institutions.